Pengaruh Kualitas Pelayanan Jasa Terhadap Kepuasan Pasien Rawat Inap (Studi Pada Rumah Sakit Militer Di Kota Malang) - Ramadhan, Randy; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to analyze the pattern of relationships by knowing the direct influence of service quality, tangibles, reliability, responsiveness, assurance and empathy for the patient satisfaction on military hospital in the city of Malang. The research presented descriptively refer to existing theories. To determine how much influence the independent variable on the dependent variable multiple linear regression analysis was used, to test analytical methods F and t test. This research used a sample of 70 patients hospitalized in the Military Hospital in Malang. While the sampling methods are purposive sampling, judgment sampling is also called the selection of a random sample types obtained by using certain considerations, generally adapted to the purpose or research problems. The results using multiple linear regression analysis, showed that simultaneous physical evidence variable (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) has a significant influence on patient satisfaction (Y) with a significance of 0.000 with a coefficient of determination (R2) of 0.619 (61.9%). While partial, variable physical evidence, reliability, responsiveness, assurance and empathy showed a significant effect on patient satisfaction with the significance of each variable of 0.238, 0.304, 0.050, 0.122, 0.250. Dominant variable for patient satisfaction are variable reliability (X2) with standardized beta coefficients 0.304. Keywords: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy, Patient Satisfaction, Hospital, Malang